Creative Industry and Economic Recovery Strategies from Pandemic Disruption - Santoso, Rudi; Fianto, Achmad Yanu Alif (Jurnal Ilmu Ekonomi Terapan, 2022)
This study aims to present a critical review of how economic and financial theory is used as a solution to rise from economic downturn during the pandemic. This article will present the implementation of economic policies and approaches from various countries in the Southeast Asia region in responding to the crisis during the pandemic. This research approach uses an exploratory qualitative research model. The results of this study present and provide an analysis of an event, thought, phenomenon, individual perception, and social activity in responding to a crisis. This study found a uniform approach used by various countries regarding economic recovery policies. Financial stimulus is given to the Small and Medium Enterprises (MSME) sector to revive an economy that is experiencing difficulties. This study also finds a similar pattern related to financial stimulus policies in 6 (six) important sectors. These efforts include: creative industri incentives, road maps, training, and partnerships with investors for development.